Method for synthesizing LDH micro-nano fiber composite material by in-situ growth method and application of LDH micro-nano fiber composite material in extraction of uranium from seawater

Through the original growth method, the LDH micro -nano -fiber composite material is synthesized, and the problems of highly selected selection of the existing seawater uranium -appointed materials under high salt conditions, limited adsorption capacity, and difficulty recycling, and achieved efficient and diverse uranium adsorptions. Recycling effect.

CN119368147APending Publication Date: 2025-01-28SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411550912.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing seawater uranium extracting materials have low selectivity under high salt conditions, limited adsorption capacity, and difficulty in recycling and utilization, making it difficult to achieve the engineering process.

Method used

The LDH micro-nano fiber composite material is synthesized through the original growth method, and the Mgal-LDH micr-nano-nano-fiber is prepared using static spinning technology, and the LDH micro-nano fiber composite is formed on the surface of the fiber surface through the water thermal method. Material.

Benefits of technology

The performance of high uranium selection, large adsorption capacity, fast adsorption rate, and easy recycling under high salt conditions have broken through the problem of single and recycling difficulty in the application form of traditional inorganic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368147A_ABST
    Figure CN119368147A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing an LDH micro-nanofiber composite material through an in-situ growth method and application of the LDH micro-nanofiber composite material in extraction of uranium from seawater, and the method comprises the following steps: carrying out blending electrostatic spinning on an LDH material, polyacrylonitrile and polyvinyl alcohol to obtain LDH micro-nanofibers, and synthesizing the LDH micro-nanofiber composite material on the surfaces of the LDH micro-nanofibers through a crystal in-situ growth method by taking MgCl2 and AlCl3 as raw materials. The LDH micro-nano fiber composite material synthesized by the method is applied to extraction of uranium in seawater. The inorganic material and the fiber material are integrated by means of blending and in-situ growth, and the inorganic material is applied in the form of the fiber material, so that the inorganic material has the advantages of diversified application forms, high adsorption capacity, high adsorption rate, good uranium selective adsorption performance, easiness in recovery and the like. The material is low in cost, simple in preparation method, stable in chemical property, easy to control in production process, capable of being applied on a large scale and good in application prospect in the fields of extraction of uranium from seawater, adsorption of uranium in wastewater and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of radioactive wastewater treatment, uranium extraction from seawater and environmental protection, and more specifically, the invention relates to a method for synthesizing LDH micro-nano fiber composite material by in-situ growth method and its application in uranium extraction from seawater. Background Art

[0002] The research on uranium extraction from seawater has a history of nearly 60 years, starting with the work of Davies et al. in 1964. The research originated from the "Project Oyster" in the UK in the 1950s. The research on the adsorption of uranium in uranium-containing wastewater has increased year by year at home and abroad. The research and development of adsorption materials at home and abroad and the research on the performance of materials in uranium extraction from seawater are all focused on the development of amidoxime adsorption materials and the adsorption performance of uranium in uranium extraction from seawater. In the past two decades, the research on uranium extraction from seawater has mainly been carried out on the basis of past research. There are few original studies or no dominant areas have been formed. In addition, the boundary of the types of uranium extraction materials from seawater is relatively obvious. The cross-relation and compositeness between inorganic (activated carbon, molecular sieves, graphene, porous ceramics, etc.), organic (silica gel, resin, fiber, biochar, etc.), minerals, microorganisms and other materials are still in a relatively weak stage. The key issue to promote the engineering process of uranium extraction from seawater is to obtain seawater uranium extraction materials with excellent performance. Uranium extraction materials need to have large adsorption capacity, fast adsorption rate, high selectivity under high salt conditions, easy elution, chemical corrosion resistance, and stable structure under mechanical force. Therefore, the development of new seawater uranium extraction materials such as composite polymer organic materials with uranium selectivity, resistance to biological contamination, and large adsorption capacity will be a breakthrough research direction in the research and development of seawater uranium extraction materials, which is highly innovative.

[0003] Since it is difficult for organic matter to achieve a significant breakthrough in adsorption capacity, it has limited adsorption capacity and relatively low thermal stability. Inorganic materials, especially those with ion exchange properties, such as clay and zeolite, usually have a larger adsorption capacity and exhibit better chemical and thermal stability. Therefore, many inorganic adsorbents have been studied for the extraction of uranium (such as UO2 2+ ). However, inorganic adsorbents and large hydrates [UO2(H2O) x ] 2+ The slow ion exchange kinetics between ions and their single application form often limit their applications. LDH compounds are well-known and widely studied layered anionic clays with good intercalation and anion exchange properties. These properties allow LDH materials to be used in various applications such as catalysts, two-dimensional nanoreactors, adsorbents and scavengers.

[0004] For the current uranium extraction, the affinity of MgAl-LDH and MgAlFe-LDH is more than twice the maximum affinity of other LDH and LDHs-based materials, and the main adsorption mechanism is surface complexation and interlayer carbonate co-precipitation. MgAl-LDH is more suitable for uranium extraction in seawater with low uranium concentration. However, inorganic materials have problems such as single form, difficulty in solid-liquid separation and difficulty in recycling adsorbents in application. It is compounded with fiber materials, with fiber as carrier and inorganic material as filler, and inorganic materials and fiber materials are integrated by blending or in-situ growth, giving inorganic materials the form of fiber materials for application, so that it can achieve the advantages of diversified application forms, high adsorption capacity, fast adsorption rate, good uranium selective adsorption performance and easy recovery. Summary of the invention

[0005] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0006] In order to achieve these purposes and advantages according to the present invention, a method for synthesizing LDH micro-nano fiber composite materials by in-situ growth method is provided, which is characterized by comprising: electrostatic spinning of LDH material, polyacrylonitrile and polyvinyl alcohol to obtain LDH micro-nano fibers, and then synthesizing the LDH micro-nano fiber composite materials by in-situ growth of crystals on the surface of LDH micro-nano fibers using MgCl2 and AlCl3 as raw materials.

[0007] Preferably, the method comprises the following steps:

[0008] Step 1, the LDH material is MgAl-LDH, and the preparation method of MgAl-LDH includes: dissolving magnesium chloride and aluminum chloride in water, stirring and dissolving to obtain a mixed solution, heating to a constant temperature, and adding a NaOH solution dropwise to the mixed solution under continuous stirring until the pH is maintained at 9 to 11; after a period of hydrothermal reaction, constant temperature crystallization is performed, and then the sample is alternately washed with ethanol and deionized water, and dried to obtain MgAl-LDH;

[0009] Step 2: Dissolve polyvinyl alcohol and polyacrylonitrile in a dimethyl sulfoxide solution in a certain proportion and mix them evenly. Stir under water at a constant temperature to dissolve the polyvinyl alcohol and polyacrylonitrile to obtain a spinning base solution. Disperse the MgAl-LDH prepared in step 1 in the spinning base solution in small amounts and multiple times. Stir under water at a constant temperature to dissolve evenly to obtain the MgAl-LDH fiber spinning solution. Prepare MgAl-LDH micro-nano fibers using electrospinning technology.

[0010] Step 3: Prepare magnesium chloride and aluminum chloride solutions of certain concentrations respectively, and take a certain proportion of Mg 2+ Solution and Al 3+The solution was stirred evenly in a beaker, and the MgAl-LDH micro-nanofibers obtained in step 2 were added, and stirring was continued. The mixture was heated to a constant temperature, and NaOH solution was added dropwise to the mixed solution under stirring until the pH value was maintained at 9-11. After a period of hydrothermal reaction, the mixture was crystallized at a constant temperature. The sample was then washed alternately with ethanol and deionized water, and dried to obtain an LDH micro-nanofibers composite material.

[0011] Preferably, in step 1, the molar concentration ratio of magnesium chloride to aluminum chloride in the mixed solution is 1 to 3:1.

[0012] Preferably, in the step 1, the hydrothermal reaction temperature is 50-80° C., and the constant temperature crystallization time is 6-18 hours.

[0013] Preferably, in the step 2, the mass ratio of polyacrylonitrile, polyvinyl alcohol, MgAl-LDH and dimethyl sulfoxide is 1-5g: 1g: 0.1-2g: 15-45g.

[0014] Preferably, in the step 2, after dispersing MgAl-LDH in the spinning base solution, the reaction temperature is 70-90° C. and the stirring time is 4-6 hours.

[0015] Preferably, in step three, the mass ratio of magnesium chloride, aluminum chloride, deionized water, and MgAl-LDH micro-nano fibers is 5-6 g: 15-17 g: 150-200 mL: 0.5-2.0 g.

[0016] Preferably, in step three, the hydrothermal reaction temperature is 50-60° C., and the constant temperature crystallization time is 6-18 h.

[0017] The invention discloses an application of a LDH micro-nano fiber composite material in extracting uranium from seawater. The LDH micro-nano fiber composite material is used for adsorbing uranium in seawater.

[0018] Preferably, the solid-to-liquid ratio of the LDH micro-nano fiber composite material to seawater is 0.01-10g:0.1-10L.

[0019] The present invention has at least the following beneficial effects:

[0020] (1) The preparation method of the LDH micro-nano fiber composite material synthesized by in-situ growth method provided by the present invention is simple and easy to operate, with mild conditions, and can realize batch synthesis. The present invention composites inorganic materials with fiber materials, uses fiber as a carrier and inorganic materials as fillers, integrates inorganic materials with fiber materials by blending or in-situ growth, and gives inorganic materials the form of fiber materials for application, so that it can achieve the advantages of diversified application forms, high adsorption capacity, fast adsorption rate, good uranium selective adsorption performance and easy recovery.

[0021] (2) The LDH micro-nanofiber composite material synthesized by the in situ growth method provided by the present invention has a large adsorption capacity of up to 360 mg / g or more, a fast adsorption rate, and reaches adsorption equilibrium within 10 minutes. It also has the ability to resist interference from multiple cations and a strong ability to selectively adsorb uranium, and can effectively adsorb uranium in wastewater and seawater.

[0022] (3) The LDH micro-nano fiber composite material synthesized by the in-situ growth method provided by the present invention can be recycled multiple times using 0.1-1 mol / L sodium chloride solution as a decomposing agent.

[0023] The advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the SEM image of the LDH micro-nanofibers prepared in step 2 of Example 1

[0025] Figure 2 is a SEM image of the LDH micro-nano fiber composite material of Example 1;

[0026] Figure 3 FTIR graph of the LDH micro-nano fiber composite material of Example 1;

[0027] Figure 4 The effect of solution pH in Example 2 on the adsorption of uranium by LDH micro-nano fiber composite materials;

[0028] Figure 5 The effect of adsorption time on uranium adsorption by LDH micro-nano fiber composite materials in Example 3;

[0029] Figure 6 The effect of the solution uranium concentration on the adsorption of uranium by the LDH micro-nano fiber composite material in Example 4;

[0030] Figure 7 The effect of adsorption time on uranium adsorption by LDH micro-nano fiber composite materials in the uranium-vanadium coexistence system of Example 5;

[0031] Figure 8 The adsorption of metal cations by the LDH micro-nanofiber composite material of Example 6 in simulated seawater. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0033] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more elements or combinations thereof.

[0034] Example 1

[0035] This embodiment provides a method for synthesizing LDH micro-nano fiber composite material by in-situ growth method, comprising the following steps:

[0036] Step 1, prepare 1 mol / L MgCl2 solution and 1 mol / L AlCl3 solution respectively, take 30 mL of MgCl2 solution and 60 mL of AlCl3 solution in a beaker, heat to 60°C under stirring, and then slowly add 2 mol / L NaOH solution until the solution pH reaches about 10, at which time an obvious white precipitate is generated. After constant temperature crystallization at 60°C for 12 hours, wash alternately with ethanol and deionized water until the filtrate is clear, and the obtained LDH precipitate is dried for use;

[0037] Step 2: Dissolve 0.7 g polyacrylonitrile and 0.1 g polyvinyl alcohol in 10 mL dimethyl sulfoxide solution and mix evenly. Heat to 80°C with stirring in water to dissolve the polyvinyl alcohol and polyacrylonitrile to obtain a spinning base solution. Evenly disperse 0.1 g of LDH in the spinning base solution in small amounts and multiple times. Stir in water at a constant temperature for 4 hours to obtain an LDH fiber spinning solution, and prepare MgAl-LDH micro-nanofibers using electrospinning technology.

[0038] Step 3, take 30mL of MgCl2 solution and 60mL of AlCl3 solution in a beaker and stir evenly, add the above-obtained LDH micro-nano fiber, continue stirring, heat to 60°C, and then slowly add 2 mol / L NaOH solution until the solution pH reaches about 10, at which time white crystals are generated on the fiber surface. After the hydrothermal reaction is completed for 12 hours, the fiber is filtered out and washed alternately with ethanol and deionized water until the filtrate is clear. After drying, the LDH micro-nano fiber composite material is obtained.

[0039] The SEM image of the LDH micro-nano fibers obtained in step 2 of this embodiment is as follows: Figure 1 As shown in FIG. 1 , the surface of the LDH micro-nano fiber obtained by electrospinning has obvious wrinkles, and the fiber diameter is in the range of 100-500 nm; the SEM image of the LDH micro-nano fiber composite material obtained in step 3 is shown in FIG. Figure 2 As shown in FIG. 1 , the surface of the micro-nanofibers after in-situ growth of LDH becomes rough, and obvious LDH crystals are generated; the FTIR images of the LDH micro-nanofibers and LDH micro-nanofiber composites obtained in steps 2 and 3 are shown in FIG. Figure 3As shown, the LDH micro-nanofiber structure contains cyanide, CH, CC skeletons of PAN, -OH, CH, CC skeletons of PVA, and interlayer species composed of double metal hydroxides and water molecules contained in LDH; the concentration of interlayer species composed of double metal hydroxides and water molecules in the micro-nanofibers after in situ growth of LDH is significantly increased.

[0040] Example 2

[0041] This example uses the LDH micro-nano fiber composite material prepared in Example 1 to simulate uranium-containing wastewater, including the following steps:

[0042] Take 25mL of simulated uranium-containing wastewater (uranium concentration is 10mg / L), and adjust the pH of the solution to 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, and 11.0. Weigh 0.01g of the LDH micro-nano fiber composite material prepared in Example 1 and place it in a sample tube containing simulated uranium-containing wastewater. React at room temperature for 60min, filter, and take the supernatant to measure the remaining uranium concentration.

[0043] The results show that if Figure 4 As shown, the adsorption performance of the LDH micro-nano fiber composite material has basically no significant change in the solution pH range of 3-9, and the adsorption rate of uranium is 99.95%; combined with the seawater pH of about 8.0, the LDH micro-nano fiber composite material still has good applicability.

[0044] Example 3

[0045] This example uses the LDH micro-nano fiber composite material prepared in Example 1 to simulate uranium-containing wastewater, including the following steps:

[0046] 25 mL of uranium solution with a concentration of 10 mg / L was placed in a sample tube, and its pH was adjusted to 8.0 with 1.0 mol / L HCl and Na2CO3 solutions. 0.01 g of the LDH micro-nano fiber composite material prepared in Example 1 was weighed and placed in a sample tube filled with simulated uranium-containing wastewater. Samples were taken at 5, 10, 30, 60, 90, 120, 180, and 240 min, respectively. After filtration, the supernatant was taken to measure the residual uranium concentration.

[0047] The results show that if Figure 5 As shown, within the adsorption time range of 5-240 min, as the adsorption time increases, the adsorption of uranium in the solution by the LDH micro-nano fibers gradually reaches equilibrium, 90% of the uranium in the solution can be adsorbed within 5 min, and the adsorption equilibrium is reached within 10 min, thus achieving rapid adsorption of uranium in the solution.

[0048] Example 4

[0049] This example uses the LDH micro-nano fiber composite material prepared in Example 1 to simulate uranium-containing wastewater, including the following steps:

[0050] 25 mL of uranium solution with concentrations of 5, 10, 20, 50, 100, 120, 150, and 200 mg / L were placed in sample tubes, and the pH was adjusted to 8.0 with 1.0 mol / L HCl and Na2CO3 solutions. 0.01 g of the LDH micro-nano fiber composite material prepared in Example 1 was weighed and placed in conical flasks filled with simulated uranium-containing wastewater. After 60 minutes of action, the supernatant was filtered and the residual uranium concentration was measured.

[0051] The results show that if Figure 6 As shown, the adsorption capacity of the LDH micro-nano fiber composite material increases with the increase of the initial uranium concentration of the solution in the range of uranium concentration of 5-200 mg / L. When the initial uranium concentration is 200 mg / L and pH = 8.0, the adsorption capacity of the LDH micro-nano fiber composite material for uranium is the largest, reaching 361.5 mg / g.

[0052] Example 5

[0053] This example uses the LDH micro-nano fiber composite material prepared in Example 1 to simulate uranium-containing wastewater, including the following steps:

[0054] Prepare 50mL of simulated wastewater 1 with a uranium concentration and a vanadium concentration of 10 mg / L, and 50mL of simulated wastewater 2 with a uranium concentration and a vanadium concentration of 50 mg / L, adjust the pH to 8.0 with 1.0mol / L HCl and Na2CO3 solution, weigh 0.01g of the LDH micro-nanofiber composite material prepared in Example 1 and place them in conical flasks filled with simulated uranium-containing wastewater, respectively, take samples at 1, 5, 10, 20, 30, 60, 120, 180, 240, and 300min, filter, and take the supernatant to measure the residual uranium concentration.

[0055] The results show that if Figure 7 As shown, in the presence of vanadium, the main competing ion in seawater, the LDH micro-nano fiber composite material still has a good adsorption rate for uranium. It can reach adsorption equilibrium in 20 minutes at low concentrations, basically achieving complete adsorption of uranium and having good anti-interference ability.

[0056] Example 6

[0057] This embodiment uses the LDH micro-nano fiber composite material prepared in Example 1 in simulated seawater, including the following steps:

[0058] 30.0 g of sea salt and 0.30 mL of uranium mother solution with a concentration of 1000 mg / L were taken, and the volume was adjusted to 1 L with deionized water to prepare simulated seawater with a uranium concentration of 0.3 mg / L, and the mass concentrations of 11 metal elements including Cu, K, Ba, Mn, Fe, Ni, Sr, Ca, Mg, V and U in the simulated seawater were measured at the same time. 0.01 g of the LDH micro-nano fiber composite material prepared in Example 1 was weighed and placed in a conical flask filled with simulated seawater. After 60 min of action, the supernatant was filtered and the mass concentrations of the remaining 11 metal elements including Cu, K, Ba, Mn, Fe, Ni, Sr, Ca, Mg, V and U in the simulated seawater were measured.

[0059] The results show that if Figure 8 As shown, the LDH micro-nano fiber composite material has good selective adsorption capacity for uranium in the presence of multiple ions, good anti-interference ability, and the highest adsorption capacity for uranium, reaching 28.92 mg / g.

[0060] The present invention forms LDH micro-nano fibers by electrostatic spinning of LDH, polyacrylonitrile and water-soluble polyvinyl alcohol, and then uses the LDH micro-nano fibers as a substrate to in-situ grow LDH crystals on the fiber surface by a hydrothermal method, and forms an LDH micro-nano fiber composite material with a high specific surface area by regulating the crystallinity and content of LDH, so that the adsorption capacity and adsorption rate of the fiber are doubled; the LDH micro-nano fiber composite material with high uranium adsorption is prepared by a simple co-spinning and hydrothermal synthesis method, and the uranium in the water body is quickly and efficiently enriched in a ion exchange manner, breaking through the bottleneck of the single application form and difficult recovery of traditional inorganic materials, and can be used as a seawater uranium extraction material with excellent performance, which helps the enrichment of uranium to a certain extent.

[0061] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.

[0062] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for synthesizing LDH micro-nano fiber composite materials by in-situ growth method, characterized in that: include: LDH material, polyacrylonitrile and polyvinyl alcohol were blended and electrospun to obtain LDH micro-nano fibers. Then, MgCl2 and AlCl3 were used as raw materials to synthesize LDH micro-nano fiber composite materials by in-situ crystal growth on the surface of LDH micro-nano fibers.

2. The method for synthesizing LDH micro-nano fiber composite material by in-situ growth method according to claim 1, characterized in that: The following steps are involved: Step 1, the LDH material is MgAl-LDH, and the preparation method of MgAl-LDH includes: dissolving magnesium chloride and aluminum chloride in water, stirring and dissolving to obtain a mixed solution, heating to a constant temperature, and adding a NaOH solution dropwise to the mixed solution under continuous stirring until the pH is maintained at 9 to 11; after a period of hydrothermal reaction, constant temperature crystallization is performed, and then the sample is alternately washed with ethanol and deionized water, and dried to obtain MgAl-LDH; Step 2, polyvinyl alcohol and polyacrylonitrile are dissolved in a dimethyl sulfoxide solution in a certain proportion and mixed evenly, and the polyvinyl alcohol and polyacrylonitrile are dissolved by stirring at a constant temperature in water to obtain a spinning base solution, and the MgAl-LDH prepared in step 1 is dispersed in the spinning base solution in small amounts and multiple times, and the MgAl-LDH fiber spinning solution is obtained by stirring and dissolving evenly at a constant temperature in water, and MgAl-LDH micro-nano fibers are prepared by using electrospinning technology; Step 3: Prepare magnesium chloride and aluminum chloride solutions of certain concentrations respectively, and take a certain proportion of Mg 2+ Solution and Al 3+ The solution was stirred evenly in a beaker, and the MgAl-LDH micro-nanofibers obtained in step 2 were added, and stirring was continued. The mixture was heated to a constant temperature, and NaOH solution was added dropwise to the mixed solution under stirring until the pH value was maintained at 9-11. After a period of hydrothermal reaction, the mixture was crystallized at a constant temperature. The sample was then washed alternately with ethanol and deionized water, and dried to obtain an LDH micro-nanofibers composite material.

3. The method for synthesizing LDH micro-nano fiber composite material by in-situ growth method according to claim 2, characterized in that: In the step 1, the molar concentration ratio of magnesium chloride to aluminum chloride in the mixed solution is 1 to 3:

1.

4. The method for synthesizing LDH micro-nano fiber composite material by in-situ growth method according to claim 2, characterized in that: In the step 1, the hydrothermal reaction temperature is 50 to 80° C., and the constant temperature crystallization time is 6 to 18 hours.

5. The method for synthesizing LDH micro-nano fiber composite material by in-situ growth method according to claim 2, characterized in that: In the step 2, the mass ratio of polyacrylonitrile, polyvinyl alcohol, MgAl-LDH and dimethyl sulfoxide is 1-5g: 1g: 0.1-2g: 15-45g.

6. The method for synthesizing LDH micro-nano fiber composite material by in-situ growth method as claimed in claim 2, characterized in that: In the step 2, after MgAl-LDH is dispersed in the spinning base solution, the reaction temperature is 70-90° C. and the stirring time is 4-6 hours.

7. The method for synthesizing LDH micro-nano fiber composite material by in-situ growth method as claimed in claim 2, characterized in that: In the step 3, the mass ratio of magnesium chloride, aluminum chloride, deionized water, and MgAl-LDH micro-nano fibers is 5-6 g: 15-17 g: 150-200 mL: 0.5-2.0 g.

8. The method for synthesizing LDH micro-nano fiber composite material by in-situ growth method as claimed in claim 2, characterized in that: In the step 3, the hydrothermal reaction temperature is 50-60° C., and the constant temperature crystallization time is 6-18 hours.

9. Application of a LDH micro-nano fiber composite material in extracting uranium from seawater, wherein the LDH micro-nano fiber composite material is prepared by the method for synthesizing the LDH micro-nano fiber composite material by in-situ growth method according to any one of claims 1 to 8, characterized in that: The LDH micro-nano fiber composite material is used for adsorbing uranium in seawater.

10. The use of the LDH micro-nano fiber composite material in extracting uranium from seawater as claimed in claim 9, characterized in that: The solid-to-liquid ratio of the LDH micro-nano fiber composite material to seawater is 0.01-10g:0.1-10L.